Investigations on doping induced changes in structural, electronic structure and magnetic behavior of spintronic Cr–ZnS nanoparticles. (July 2015) - Kaur, Palvinder; Kumar, Sanjeev; Singh, Anupinder; Chen, C.L.; Dong, C.L.; Chan, T.S.; Lee, K.P.; Srivastava, C.; Rao, S.M.; Wu, M.K.
Highlights: Cr doped ZnS nanoparticles crystallized in the zinc blende (cubic) structure with no secondary phase. XANES studies depict that the valence of Zn is not changed but maintained in the same divalent state upon doping with Cr. Photoluminescence and Raman studies show the incorporation of Cr dopant in host ZnS nanoparticles. Doping of Cr in ZnS nanoparticles gives rise to ferromagnetic ordering at room temperature. Abstract: Dilute magnetic semiconducting Zn1− x Cr x S ( x  = 0.00, 0.01, 0.03, 0.05, 0.07) nanoparticles were synthesized by the co-precipitation technique using thioglycerol as the capping agent. Powder X-ray diffraction studies showed that Zn1− x Cr x S nanoparticles exhibit zinc blende structure with no secondary phase, indicating that Cr ions are substituted at the Zn sites. Photoluminescence and Raman studies show the incorporation of Cr in ZnS nanoparticles. X-ray absorption studies depict that the valence of Zn remains unchanged and maintained in the divalent state, upon doping with Cr. The M–H curves at room temperature indicate the presence of weak ferromagnetism at room temperature due to structural defects. The increase in ferromagnetism with increasing Cr content up to 3%, demonstrates the possibility of tailoring the weak ferromagnetism in ZnS by appropriate Cr doping.